Directional statistics - Mardia, Kanti V; Jupp, Peter E (Chichester John Wiley, 2000)
Directional statistics gives a unified and comprehensive account of directional statistics,presenting both the underlying statistical theory and the practical methodology.The book is divided into three parts.The first part concentrates on statistics theor
Keywords: Mathematical statistics; Distribution (Probability theory); Sampling (Statistics)